Assessing intern handover processes. (18th June 2015) - Habicht, Robert; Block, Lauren; Silva, Kathryn Novello; Oliver, Nora; Wu, Albert; Feldman, Leonard
Summary: Background: New standards for resident work hours set in 2011 changed the landscape of patient care in teaching hospitals, and resulted in new challenges for US residency training programmes to overcome. One such challenge was a dramatic increase in the number of patient handovers performed by residents. As a result, there is a renewed focus for clinical teachers to develop educational strategies to optimise the patient handover process and improve the quality of patient care and safety. Methods: In order to investigate current gaps in resident handovers, we examined the handover processes performed by medicine interns at two academic medical centres in Baltimore, Maryland, USA. We used trained observers to collect data on whether handovers were conducted face to face, with questions asked, in private locations, with written documentation, and without distractions or interruptions. Results were analysed using chi‐square tests, and adjusted for clustering at the observer and intern levels. Results: Interns successfully conducted handovers face to face (99.5%), asked questions (85.3%), used private locations (91%), included written handover documentation (95.8%) and did not experience distractions for the majority of the time (87.7%); however, interruptions were pervasive, occurring 41.3 per cent of the time. In order to investigate current gaps in resident handovers, we examined the handover processes performed by medicine interns Discussion: Interns conducted patient handovers face to face, with questions asked, in private locations, with written documentation and without distractions the majority of the time; however, interruptions during the handover process were common. Exploring gaps at the individual programme level is a critical first step to develop effective teaching strategies to optimise handovers in residency.